The Tax Treatment of Employee Stock-Options: A Brazilian Perspective - Accorsi Voss, Agatha (PANORAMA OF BRAZILIAN LAW, 2019)
The article presents an analysis of issues concerning the taxation of employee stock options plans (ESOPs). It examines a detailed study published by the Organization for Economic Co-operation and Development (OECD) regarding the tax treatment of stock options and incentive pay schemes in the OECD countries and compares its conclusions with the tax treatment of ESOPs in Brazil. The aim of the article is to illustrate the main conclusions of the analysis made by OECD based on the tax neutrality principle and to provide a specific description of the tax treatment of ESOPs in Brazil, showing how the discussions pointed out by OECD are being faced in the country. The conclusion, unfortunately, is that all the intricacies that arise when the companies decide to grant ESOPs listed by OECD also arise in Brazil, which combined with the fact that there are no specific regulations regarding the tax treatment of stock options, specially regarding the qualification of the income received by employees as stock options (if salary or only capital gains), introduces even more an undesired level of uncertainties.